Investigating the Growth of Human Resource Performance Empowerment in the Economic Development of Future Cities in Tourist Destinations - Ebadi Moayyed, Mehdi; Aref, Ali Akbar; Kabiri, Morteza; Tirandaz, Mohammadsadegh (International Journal of Innovation Management and Organizational Behavior (IJIMOB), 2024)
Objective: This research aims to examine the empowerment of human resource performance in the economic development of future cities in tourist destinations. Methodology: Thus, this study is considered applied research in terms of its objective. Moreover, from the perspective of data collection and analysis, the current research is descriptive-correlational. The statistical population of this study includes employees and managers of municipal areas in 15 districts of Isfahan. To this end, 2687 individuals were registered, who were investigated as the research population. Based on Morgan’s table, 337 individuals were selected using random sampling method. Measurement of the variables of human resource performance empowerment and urban economic development was conducted using a questionnaire. Fuzzy TOPSIS was employed in Excel software environment for ranking the factors, and likewise, the hypothesis testing was performed using the structural equation modeling method and statistical software including Smart PLS and SPSS. Findings: The findings indicate a significant effect of human resource performance empowerment on urban economic development. Therefore, in order to empower employees in the organization, proper and initial infrastructure within the organizational environment is required. Conclusion: In organizations where influential factors in empowerment are fully and correctly implemented, it can be ensured that the best use of human resources is made, resulting in the highest efficiency in the organization.